Ultrasound-induced remediation of the second-generation antihistamine, Cetirizine. Issue 3 (June 2020) - Cui, Danni; DeCaprio, Anthony; Tarifa, Anamary; O'Shea, Kevin
Highlights: Cetirizine is rapidly degraded by ultrasonic irradiation. The degradation is the result of hydroxyl radical and pyrolysis mediated pathways. The kinetics follow the Langmuir-Hinshelwood model. Product studies show hydroxylation of the aromatic rings and fragmentation pathways. Abstract: Cetirizine, a second-generation antihistamine, has been detected in surface water and wastewater treatment eluent. The presence of Cetirizine and personal care products in the sources for drinking water is a serious concern. Cetirizine in aqueous media is readily degraded over a wide range of concentrations (4.3 to 65 μmol/L) upon ultrasonic treatment at 640 KHz. When the concentration of CET was below 21.7 μmol/L, more than 50 % of the initial concentration was degraded within 12 min. The degradation is effectively modeled at individual concentrations by pseudo first order kinetics, however the rate constants varied from 0.148 to 0.025 min −1 as a function of initial concentration. The degradation kinetics are effectively modeled by Langmuir-Hinshelwood heterogeneous kinetics. Application of the L=H model to the ultrasonic induced degradation of Cetirizine yields a reactivity constant, kL-H-rxn  = 1.64 μmol· L −1 · min −1 and the partitioning constant, KL-H  = 0.10 L/μmol. Ultrasonically induced degradation of Cetirizine was faster under argon and oxygen saturated conditions compared to air saturation. Addition of an equimolar concentration of the hydroxyl radical scavenger, coumarin, during ultrasonic treatment lead to decreased degradation rates by 46 %, demonstrating that pyrolysis and hydroxyl radical oxidation significantly contribute to the degradation process. The primary degradation reaction products, 1-((4-chlorophenyl)(phenyl)methyl)piperazine, 2-(2-(piperazin-1-yl)ethoxy)acetic acid, 2-(4-((4-chlorophenyl)(phenyl)methyl)piperazin-1-yl)ethanol, and ortho, meta and para hydroxylation of the aromatic ring of CET were identified by LC–MS. Ultrasound induced remediation is a rapid and effective method for remediation of Cetirizine from water.